Technology for processing predicted frames of the video stream for on-board information technologies - Бараннік, В. В.; Тарасенко, Д. А.; Медвєдєв, Д.О.; Хіменко, В.В. (Science-based technologies, 2017)
The necessity of development of technologies for efficient syntactic representation of video frame segments is substantiated on the basis of constructing a densified two-dimensional structural spectral space (DSP). The informative value of the identifier vector of the coordinate objects of the DSP of the transformant space is estimated. The development of an effective syntactic representation of transformants based on one-dimensional two-base object-position coding in conditions of flexible inequality of pair elements is described. The synthesis of the system of relationships forming the technological core of the effective syntactic representation of the segment of the video frame is based on: the formation of a densified two-dimensional spectral structure space with the subsequent one-dimensional two-base object-positional coding in the identifier space under conditions of flexible presence of the pair-element inequality.